Strategi Pemanfaatan Media Air (Hidroponik) Pada Budidaya Tanaman Kangkung, Pakcoy, Dan Sawi Sebagai Alternatif Urban Farming - Yulia Tri Samiha (Departement of Mathematics Education, 2023)
This article aims to examine the Strategy for Utilizing Water Media (Hydroponics) in the Cultivation of Kale, Pakcoy, and Mustard Greens as an Alternative to Urban Farming. Plant cultivation using a hydroponic system is a method of farming without using soil. Water, light, and nutrition are three important elements in cultivating plants through a hydroponic system. A more controlled environment and simpler planting media make the hydroponic system an alternative or means of implementing urban farming which is increasingly popular today. This research was conducted using the hydroponic method which uses a hydroponic culture system to plant through a hydroponic system. This system provides more profitable growth in a growing environment. Data collection as a reference in this study was carried out using primary and secondary methods, namely primary data collection through field activities and secondary data through the library, namely utilizing secondary data obtained from various literature such as books, journals, official documents, websites, and so on. The results of this study found that hydroponic vegetable cultivation is more productive than conventional vegetable cultivation, as evidenced by extensive land use and productivity. One of the reasons for the increasing need for food is urbanization which has led to the importance of productive plant cultivation media, such as hydroponics.